Restless Legs Syndrome in Multiple Sclerosis - Zecca, Chiara; Manconi, Mauro; Fulda, Stephany; Gobbi, Claudio (CNS & Neurological Disorders - Drug Targets, 2012)
There is a growing interest in sleep disorders in multiple sclerosis (MS) due to their high frequency and possible relationship to fatigue, a hallmark symptom in MS. Among them, insomnia and restless legs syndrome (RLS) are the most common ones. RLS is a sleep-related motor disorder characterized by a strong urge to move associated with uncomfortable sensations in the limbs. It is frequently under diagnosed in patients with MS although its course is often particularly severe. Several arguments support a symptomatic origin of RLS in MS patients. Independently of any causal relationship, the high prevalence of RLS in MS patients has clinical implications. The purpose of the present review is (i) to summarize the epidemiological data and clinical characteristics of RLS in MS patients in order to increase sensitivity to this disorder; (ii) to document the substantial body of evidence in support of a symptomatic origin of RLS in MS and from this (iii) to delineate the proposition that MS may represent a clinical model to study RLS-associated pathological changes.
Keywords: restless legs syndrome